Understanding Riba, Product Knowledge, and Attitudes: Influences on Intentions to Become Sharia Bank Customers - Indri Yuliafitri; Ressy Siti Lathifah (Institut Agama Islam Negeri Kendari, 2022)
This study aims to examine the influence and understanding of the community about Islamic banks on the decision to become a customer of Islamic banks. The data collection technique in this research is using a questionnaire. The data collection technique used in this study. In comparison, the data analysis method uses quantitative description. The study results show that individual understanding of usury and product knowledge does not affect the intensity of being a Sharia bank customer. Attitudes towards Islamic banks affect the intensity of being a customer of Islamic banks. Meanwhile, understanding usury, product knowledge, and attitudes towards Islamic banks affect the intensity of becoming a customer.